The Effectiveness of Turmeric (Curcuma domestica) in Decreasing The Risk of Atherosclerosis - Ar Rahmah, Arsyka Hunjri (Preventif : Jurnal Kesehatan Masyarakat, 2019)
Every year more than 36 million people die due to Non-Communicable Diseases (NCD). Globally, the number one cause of death for NCD every year is cardiovascular disease. Coronary heart disease, heart failure, hypertension and stroke are cardiovascular diseases. Atherosclerosis can be a cause of cardiovascular disease. One of the therapies that can be done to treat atherosclerosis is curcumin compound. Curcumin is an active compound in turmeric (Curcuma domestica) which functions in reducing cholesterol, antioxidant, antitoxin and anti-inflammatory. Therefore, the potential effect of curcumin can be an alternative therapy to reduce the risk of atherosclerosis. This study aims to prove the effectiveness of turmeric as an alternative therapy in reducing the risk of atherosclerosis. This type of research is a descriptive form of literature study that is made using secondary data in the form of sources obtained from library studies. The method used is collecting research results from various journals, case reports and research articles. From several studies conducted on humans, curcumin is safe to use and does not show toxic effects up to a dose of 500 mg given 2 times a day for 30 days. Curcuminoids found in turmeric have benefits as anti-inflammatory and antioxidant so that they can be used as alternative therapies for atherosclerosis.